Исследование по определению 10-10 - 10-8 % Cu, Bi, Sb, Pb, Cd, Zn, Sn в арсениде галлия, галии и мышьяке - Каплин А. А. Анатолий Александрович; Михайлова З. С.; Пичугина В. М.; Стромберг А. Г. Армин Генрихович (1970, 1970)
В фонде НТБ ТПУ отсутствует